Another Look at John Marshall and the Ju/'hoansi: Reassessing a Documentary Lifetime. Issue 2 (15th March 2021) - Tomaselli, Keyan G.
Abstract : A reassessment of the Marshall family expeditions in the 1950s and the films in the Kalahari is offered. What was learned by the Marshalls, as pioneers of visual anthropology, is examined through the investigations of several later scholars, filmmakers and archivists. This article draws on the semiotics of C. S. Peirce in light of his discussion of how things appear (phaneroscopy), backgrounded research and image ethics, and my own field work amongst Kalahari Desert communities. It examines the principles and contradictions that arise from the Marshalls' research and imaging with the Ju/'hoansi people. Some new semiotic insights regarding representation and researcher position, and observer–observed relationships, are offered here.